Young Girl as Seen in Anne Frank’s The Diary of A Young Girl - Gustiani, Widia; Yuli Astuti, Amelia (Jurnal Ilmiah Langue and Parole, 2023)
This research is motivated by the existence of personality forms and cool rooms that are hiding places where Anne's maturity grows, which is realized by the mob in Anne Frank's novel The Diary of a Young Girl. The purpose of this study is to identify Anne's personality form, analyze the shape of the foreign space where Anne's maturity grows in Anne Frank's novel The Diary of a Young Girl. The method with the research is descriptive qualitative research and the approach used is literary psychology with psychology literature Sigmund Freud theory. The data in this novel are excerpts from words, sentences related to the personality of Anne's character and forms of foreign space that affect Anne's maturity growth. The data collection techniques in this study were reading, marking the data, recording and distinguishing the data collected based on Anne’s personality and foreign space that influenced Anne’s maturity in Anne Frank novel The Diary of a Young Girl. The result of this study indicate that in the novel The Diary of a Young Girl by Anne Frank, the personality experienced by Anne Frank by is more Id than the Ego and Superego, this is due to the difference in her Mother’s love between herself and older sister, and the form of foreign space that affects Anne Frank maturity is a room called the Secret Annex.